Edukasi Pemakaian Masker, Peningkatan Pengetahuan Tentang Penyakit Pernapasan, Dan Skrining Kesehatan - Machrumnizar Machrumnizar; Suriyani Tan (CV. Multi Kreasi Media, 2024)
More than four million people die each year from respiratory problems, which also affect hundreds of millions more. This disease has detrimental effects on the family, society, and the health and well-being of the patient. especially those living in low- and middle-income countries, where people are daily exposed to indoor air pollution from solid fuels used for cooking and heating. The biggest significant risk factor for respiratory disease in high-income countries is tobacco use. WHO data for 2020 shows that Lower Respiratory Infection Disease and Chronic Obstructive Pulmonary Disease rank number 3 and 4, at 6.1% and 5.8% respectively. There are eight lung diseases that are a public health problem in Indonesia and are included in the scope of the Indonesian Ministry of Health's environmental health and disease control program, including Tuberculosis, Acute Respiratory Infection (ARI), Bronchial Asthma, Lung Disease, Chronic Obstructive, Lung Cancer, Air Pollution and Climate Change, Combating Smoking Problems, Emerging & New Emerging Diseases (including COVID-19). Since WHO declared the COVID-19 pandemic in March 2020, Indonesia has carried out public interventions to stop the pandemic, including pharmaceutical and non-pharmaceutical actions (wearing masks, travel restrictions, closing schools, and postponing public events). Non-pharmaceutical interventions have a greater impact on infectious diseases than pharmaceutical interventions, despite the fact that pharmaceutical strategies can target specific organisms.